2018
DOI: 10.1017/thg.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Four-Generation Pedigree of Monozygotic Female Twins Reveals Genetic Factors in Twinning Process by Whole-Genome Sequencing

Abstract: Familial monozygotic (MZ) twinning reports are rare around the world, and we report a four-generation pedigree with seven recorded pairs of female MZ twins. Whole-genome sequencing of seven family members was performed to explore the featured genetic factors in MZ twins. For variations specific to MZ twins, five novel variants were observed in the X chromosome. These candidates were used to explain the seemingly X-linked dominant inheritance pattern, and only one variant was exonic, located at the 5'UTR region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Many attempts to identify the gene or genes and mechanism or mechanisms for their familial form of MZ twinning have been undertaken, but the mechanism(s) have not been determined (Shur, 2009). One X‐linked dominant family has also been reported (Liu et al, 2018).…”
Section: Types Of Mz Twinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts to identify the gene or genes and mechanism or mechanisms for their familial form of MZ twinning have been undertaken, but the mechanism(s) have not been determined (Shur, 2009). One X‐linked dominant family has also been reported (Liu et al, 2018).…”
Section: Types Of Mz Twinsmentioning
confidence: 99%
“…Harvey et al (1977); Parisi et al (1983) suggested there might be rare families in which a form of familial MZ twinning occurs. Recently, clusters of familial MZ twinning have been identified in India and Brazil (Cyranoski, 2009; Liu et al, 2018; Machin, 2009a, 2009b; Matte et al, 1996). These familial MZ twins appear NOT to have an increase in congenital anomalies, nor has TTTS been reported in spite of single placentas.…”
Section: Types Of Mz Twinsmentioning
confidence: 99%
“…But indeed, monozygotic twinning occurs at a relatively constant rate of three to five in 1,000 births worldwide, supporting the view that it represents a random and/or genetic event (Tarlatzis et al, ). A paper by Liu et al () described a four‐generation pedigree of monozygotic female twins revealing novel genetic variants specific to monozygotic twins in the X chromosome.…”
Section: Etiology and Pathogenesis Of Conjoined Twinsmentioning
confidence: 99%
“…On the other hand, Echternkamp, Thallman, Cushman, Allan, and Gregory (2007) and Morris et al (2010) selected lineages for multiple ovulation, with the consequent increment in conception rate (DZ twins or multiple births). While the inheritance of MZ twins in cattle has not been reported and has been discussed for decades in many species, some works in human beings suggest a genetic background (Liu et al., 2018; Machin, 2009). If those same mechanisms are presented in cattle, the female in the current study and her daughters could be the founders of a lineage to study a possible genetic or epigenetic mechanism behind MZ multiple births in cattle.…”
Section: Introductionmentioning
confidence: 99%